2019
DOI: 10.1177/1478929919847132
|View full text |Cite
|
Sign up to set email alerts
|

Consultant Lobbyists and Public Officials: Selling Policy Expertise or Personal Connections in Canada?

Abstract: Recent research suggests that there are two different types of lobbyists: those specializing in providing access to their personal connections with public office holders, and those specializing in a particular policy sector. This article advances this research by examining the actual behaviour of consultant lobbyists with data gathered from the Canadian Lobbyist Registry. Specifically, we probe two questions. First, using four indicators found within the literature, we investigate whether the behaviour of cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 57 publications
(46 reference statements)
2
32
0
Order By: Relevance
“…To some, therefore, the issue arising from the careers of MAs is not that they are part of a detached political class but, rather, that they can use insights and skills – ‘specialized human capital’ (Parker et al, 2012) – acquired while serving in public office to obtain high positions outside of politics. This so-called revolving-door problem captures the practice of former politicians migrating to jobs where the insights, networks and other resources they have obtained in high-octane politics can give their new employers a competitive advantage (Boucher and Cooper, 2019; Parker et al, 2012; Selling and Svallfors, 2019). For example, politicians are cognisant that external actors can effectively influence government decisions about subsidies, procurement and regulation (Cohen, 1986).…”
Section: Career Perspectives On Ministerial Advisorsmentioning
confidence: 99%
See 1 more Smart Citation
“…To some, therefore, the issue arising from the careers of MAs is not that they are part of a detached political class but, rather, that they can use insights and skills – ‘specialized human capital’ (Parker et al, 2012) – acquired while serving in public office to obtain high positions outside of politics. This so-called revolving-door problem captures the practice of former politicians migrating to jobs where the insights, networks and other resources they have obtained in high-octane politics can give their new employers a competitive advantage (Boucher and Cooper, 2019; Parker et al, 2012; Selling and Svallfors, 2019). For example, politicians are cognisant that external actors can effectively influence government decisions about subsidies, procurement and regulation (Cohen, 1986).…”
Section: Career Perspectives On Ministerial Advisorsmentioning
confidence: 99%
“…Scholarship utilizing a career rewards perspective has shown that monetary and visible rewards for high public office 'do not extinguish with [the] end of tenure but rather provide new credentials which expand [politicians'] ability to fulfil their career ambitions' (Claveria and Verge, 2015: 819; see also Brans and Peters, 2014). The potential revolving-door problem refers to former politicians migrating to jobs where their insights entail a competitive advantage for employers (Boucher and Cooper, 2019;Parker et al, 2012;Selling and Svallfors, 2019).). However, little is known about what aspects of their work in the core of executive government make MAs attractive to outside employers (Hustedt et al, 2017;Wilson, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, EU consultancy research might engage with the burgeoning debate that addresses the role of consultants to IGs. If buying access is not the key motivator, to what extent do other factors, namely the need for information on political processes or policy expertise drive consultancy hiring (Boucher and Cooper, 2019; Lapira, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…American research (LaPira and Thomas 2017) suggests that whereas in-house lobbyists tend to be experts on a particular issue, and form stable relationships with government agencies as they lobby on the same issue over time, consultant lobbyists are better described as "well-connected chameleons," selling access to government personnel to any interested party. Using the registry, Boucher and Cooper (2019) investigate whether this description of consultant lobbyists applies to Canada, and find a more complex story playing out. Although the majority of consultant lobbyists behave in ways consistent with being issue experts, a sizeable minority contact public office holders across a vast range of policy sectors and maintain enduring relationships with "moving" public office holders-which is consistent with selling access as connectionpeddling generalists.…”
Section: What Characteristics Define Lobbyists? What Are Lobbyists' Objectives?mentioning
confidence: 99%